789 Intratumoral plasmid IL-12 expands CD8+ T cells and induces a clinically validated CXCR3 signature in triple-negative breast cancer. (9th November 2020) - Crosby, Erika; Nagata, Hiroshi; Telli, Melinda; Acharya, Chaitanya; Wapnir, Irene; Zablotsky, Kaitlin; Browning, Erica; Hermiz, Reneta; Svenson, Lauren; Bannavong, Donna; Malloy, Kellie; Canton, David; et al.
Abstract : Background: Triple-negative breast cancer (TNBC) is an aggressive disease with limited therapeutic options. Immune checkpoint inhibitors (ICI) have entered the therapeutic landscape in TNBC, but only a minority of patients benefit. Interleukin-12 (IL-12) is a pro-inflammatory cytokine involved in the generation of an inflammatory tumor microenvironment and is critical in eliciting a productive anti-tumor immune response. It has been investigated as an anti-cancer therapeutic using various delivery routes, but intratumoral injection of plasmid IL-12 (tavokinogene telseplasmid; tavo) followed by electroporation is a gene therapy approach with minimal systemic immune-related toxicity. Methods: Intratumoral injection of tavo was tested in several preclinical models of TNBC and single cell RNA sequencing (scRNAseq) was used to evaluate changes in the tumor microenvironment following treatment. These findings were then applied to the analysis of patient samples from a single arm, prospective clinical trial of tavo monotherapy (OMS-I140; NCT02531425 ). Results: A comprehensive analysis of cellular networks using ligand-receptor interactions identified CXCR3 (expressed by APCs) to be positively correlated with CXCL9/10/11 secreted by CD8 T cells. Further investigation of tavo treated murine tumors resulted in a 50-gene CXCR3 gene expression signature that is associated with a decrease in granulocytes, enhanced antigen presentation, increased T cell infiltration, and induction of PD-1/PD-L1. A deeper look at paired TCR alpha and beta chains on tumor infiltrating T cells (TILs) demonstrated a dramatic shift in TIL clonality and frequency following tavo treatment. There was a significant increase in not only the number of expanded (>10) clones, but also a robust activation signature that was absent in control tumors. Treatment of mice with tavo prior to anti-PD1 therapy led to complete tumor regression and long-term survival in a significant proportion of mice, while none of the mice treated with anti-PD1 alone exhibited this therapeutic efficacy. As a proof of concept, we utilized nanostring data from OMS-I140 to show a significant enhancement in this signature in patients who demonstrated a greater than 2-fold increase in CD8 TILS by IHC post-treatment. Further, we show a single patient who had previously been non-responsive to ICI that went on to receive anti-PD1 as their immediate next treatment after participating in OMS-I140, and demonstrated a significant clinical response. Conclusions: Together these data identify a clinically relevant CXCR3-associated gene signature that represents both a potential biomarker for response to ICIs and a potentially targetable pathway for therapeutic intervention in TNBC. Ethics Approval: All animal studies described were approved by the Duke University Medical Center Institutional Animal Care & Use Committee (A198-18-08) and performed in accordance with established guidelines.